Modified Exposure and Response Prevention to Treat the Repetitive Behaviors of a Child with Autism: A Case Report - Brian A. Boyd; Cooper R. Woodard; James W. Bodfish (Case Reports in Psychiatry)
We report the case study of a school-aged child with autism whose repetitive behaviors were treated with a modified version of a technique routinely used in cognitive behavior therapy (i.e., exposure response prevention) to treat obsessive-compulsive disorder. A trained behavioral therapist administered the modified ERP treatment over the course of an intensive two-week treatment period with two therapy sessions occurring daily. The treatment was successful at decreasing the amount of child distress and cooccurring problem behavior displayed; however, the child's interest in the repetitive behavior eliciting stimulus (i.e., puzzles) remained. The case study demonstrates specific ways that exposure response prevention strategies can be adapted to the unique kinds of repetitive behaviors that present clinically in autism. A larger clinical trial is needed to substantiate these findings.